(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of Social Media Marketing and Brand Image on Purchase Decisions with Purchase Intention as an intervening variable in consumers of Dikala Kopi Gajahmada. The research method used is a survey with primary data collection through questionnaires to 160 respondents who have interacted with social media and Dikala Kopi products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that Social Media Marketing and Brand Image have a significant effect on Purchase Intention. Social Media Marketing also has a significant direct effect on Purchase Decisions, while the direct effect of Brand Image on Purchase Decisions is not significant. However, Purchase Intention is proven to significantly mediate the relationship between Social Media Marketing and Brand Image on Purchase Decisions. This finding emphasizes the importance of managing social media and brand image in increasing consumer purchase interest which ultimately drives purchase decisions. The practical implication of this study is that Dikala Kopi is expected to optimize its marketing strategy through social media and strengthen its brand image to increase consumer purchase interest and purchase decisions.